Anchorage capacity reliability and redundancy optimization research in coastal ports. Issue 5 (4th May 2021) - Guo, Zijian; Xu, Yunzhuo; Yu, Yong; Wei, Zhijun; Xue, Tianhan; Wang, Wenyuan; Jiang, Ying
ABSTRACT: Influenced by various random factors, such as a ship's size, arrival time and anchoring spot, the number of ships that can be practically accommodated by the anchorage of a coastal port is generally far lower than the designed anchorage capacity. To address the shortage problem, this article applies a redundancy optimization theory to realize a reasonable and practical design of the anchorage capacity. A new concept of anchorage capacity reliability and its calculation method, via an anchorage capacity probability evaluation model, are proposed. A multi-objective optimization model with maximum anchorage capacity reliability and minimum anchorage redundant area is established. Furthermore, a case study of a container terminal in northern China is adopted to verify the performance of the proposed concept and methodology. Model results show that anchorage capacity reliability can effectively reflect the anchorage capacity uncertainty, and the redundancy optimization model can help to reasonably determine the anchorage capacity.